Mouse models of otitis media: strengths and limitations. - Bhutta, M (2012)
There has been a rapid rise in the use of the mouse to investigate pathobiology of otitis media. This is for good reason, including easy husbandry, but also capacity for genetic manipulation of the mouse. Insights into human disease have been gleaned from mouse models, but there are limitations of the mouse-to-man approach. First, important differences exist between mouse and man, particularly in immune function. Second, functional equivalence of genes in the 2 species is not ensured. Third, laboratory mice of a uniform genetic background and environment are an inadequate model of the plethora of factors affecting complex disease in humans. Finally, gene function in mouse models is often obliterated using gene knockout technology, but this is a poor mimic of normal gene variation in man. These drawbacks of the mouse may in the future limit its usefulness in otitis media research.